Os cómodos do Museu Casa de Rui Barbosa enquanto museália - Aparecida Marina de Souza Rangel; Álea Santos de Almeida (Midas: Museus e Estudos Interdisciplinares)
This article presents partial results of the research project “Development of a Methodology for Cataloguing the Environments of a Museum-house, Understood as Museum objects”, developed within the scope of the “Program of Incentive to the Production of Technical and Scientific Knowledge in the Cultural Area of the Casa de Rui Foundation Barbosa”. This study, still under development, seeks to understand the rooms of Museu Casa de Rui Barbosa (Rio de Janeiro, Brazil) as museum objects with the ultimate goal of developing a methodology for researching, inventorying and documenting these environments. In order to understand the rooms as museum objects, firstly we characterize them briefly to demonstrate the importance of these environments in the trajectory of the house of the patron Rui Barbosa (1849-1923), and its value as testimonies of a historical and social context. We also discuss the notion of the rooms as museum objects and the implications of this understanding in the field of Museology. The research methodology relies on literature review about the conceptual model of house museums, bibliographical research about the Museu Casa de Rui Barbosa, and inventory and museum documentation. At this phase, the research conducted demonstrates the relevance of perceiving the house museum rooms as museum objects, a new framework in the context of this typology of museum. We argue that this approach can contribute to expand the study of museum documentation in house museums.